Irrigação de plantas de meloeiro amarelo com água salina enriquecida com CO2 - Barros, Josivânia Rodrigues (2015)
Salt excess in the soil solution is a serious problem in agriculture, caused mainly by irrigation water, causing soil salinization. These salts, when absorbed affects the growth of plants because of the osmotic effect, reducing the absorption of water in the soil. In order to mitigate the deleterious effects of these salts in plants, several strategies have been developed in order to make plants most tolerant to salt stress. A recent innovation in plant cultivation system is the enrichment of irrigation water with carbon dioxide (carbonation), influencing the commercial crop yield and making them more tolerant to stresses. The objective of this study was to evaluate whether the application of CO2 in irrigation water of melon plants increases the tolerance of the same to salt stress. The experiment was conducted in Pacajus Experimental Field of Embrapa Tropical Agroindustry. The treatments were arranged in a factorial 5 x 3 with four replications, referring to salt solutions at electrical conductivities of (ECw) (0.5, 1.5, 3.0, 4.5 and 6.0 dS m-1) and three treatments with CO2: no CO2 (SC), five applications of CO2 (since flowering until the beginning ripening of fruits) (C1) and two applications of CO2 (since fruit set until the ripening of fruits) (C2). The CO2 was used as a gas injected weekly directly in the irrigation system. The electrical conductivity of the soil saturation extract and CO2 content in the irrigation water were measured at the end of the experiment. The measurement of photosynthesis, stomatal conductance and transpiration occurred throughout plant development. Were also evaluated leaf area, dry weight of leaves and stem + branches, levels of Na+, Cl-, K+ and carbohydrates in the leaves and stems + branches, the number of fruits, productivity, weight, lengths and diameters of the fruit, pulp thickness, total soluble solids and citric acid content. Leaf concentrations of Na+, Cl- and K+ in the leaf and stem + branches were influenced by salinity, with interaction salinity x CO2. For the growth variables: leaf area, dry matter of leaves and stem + branches, there was a significant difference only for the salinity levels. All variables of gas exchange were influenced by salinity, while the stomatal conductance and net photosynthesis were significantly influenced by the application of CO2. The carbohydrate in stem + branches were influenced by the application of CO2. Irrigation with saline water caused a reduction in productivity, number of fruits, lengths of commercial and total fruits. These variables were not influenced by the application of CO2. It is concluded that salinity affected the growth, development and production of melon plants, while the application of CO2 did not minimize the deleterious effect of salts in plants.